DOSE-DEPENDENT INFLUENCES OF VANILLIC ACID ON COGNITIVE FUNCTION AND REDOX HOMEOSTASIS STATUS IN N-NITROSODIETHYLAMINE TREATED DROSOPHILA MELANOGASTER - KANI, AKSHAYA; SUBRAMANIAN, PERUMAL (International Journal of Current Pharmaceutical Research, 2021)
Objective: To assess the dose-dependent effect of vanillic acid on cognitive behavior and indices of redox homeostasis in the fruit fly, Drosophila melanogaster. Methods: In this study, flies were divided into five groups-group 1 control, group 2-treated with 0.01% NDEA through drinking water for 15 w, group 3-treated with NDEA and vanillic acid (VA) (0.005%) in culture medium, group 4-treated with NDEA and VA (0.01%) and group 5-treated with NDEA and VA (0.05%). Cognitive-behavioral assays and assessment of redox homeostasis indices were performed. Results: Behavioural abnormalities (negative geotaxis, phototaxis, smell and taste chemotaxis, hypotaxis and thermotaxis) were quantitatively deviated in NDEA treated flies compared to control but were tend to be normalized in VA treated flies. The contents of protein carbonyl, thiobarbituric acid reactive substance (TBARS), protein thiol and lipid peroxides were noticeably augmented in NDEA treated flies than control flies and correspondingly tend to normalize in VA (0.01%) treated groups. Further, superoxide dismutase (SOD), catalase (CAT), glutathione-S-transferase (GST), glutathione peroxidise (GPX) and reduced glutathione (GSH) were decreased in NDEA treated group and were significantly increased (p<0.05) in VA treated (0.01%) groups. Conclusion: Vanillic acid, a bioactive phytochemical could act as a potent antioxidant and as well exhibit antiproliferative characteristics. The dose lower than 0.01% could not be effective as the dose is low. Nevertheless, at 0.01% the maximum benefits could have been achieved, and beyond this saturation point, higher doses, such as 0.05% could not be effective.